Sequence and hierarchy in discourse organization - Stoll Dougall, Pamela (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1996)
This paper discusses the sequential and hierarchical dimensions of discourse as understood from differing standpoints by conversation analysis and discourse analysis. Section 1 is devoted to the conception of discourse as a linear sequence, which enables the description of the internal structure of exchanges, while section 2 concerns itself with the notion of hierarchy, more suitable for examining the internal structure of moves. In section 3 the functional hierachical discourse model put forward by Roulet et al. (1987) is considered as a synthesis of both approaches supplying a framework for the description of both the linear and hierarchical nature of discourse, monologal as well as dialogal. Section 4 examines one case of implicit dialogism in written monologue, providing a brief illustration of the type of analysis rendered by that discourse model.